KEBIJAKAN SEKOLAH ADIWIYATA SEBAGAI PENERAPAN PENDIDIKAN KARAKTER DI SMP TELKOMUNIKASI PEKANBARU - Nasrianti, Reni; Saputra, Waldi; Zalisman, Zalisman; Akhyar, Yundri; Puspita, Yenda (STKIP Pesisir Selatan, 2023)
The fading of character values among students today makes things developed by future generations to come in the school environment such as a lack of care for the surrounding environment, littering, paying attention to school walls and student morale. The purpose of this study was to analyze the Adiwiyata school policy and the success of character education in Telecommunications Junior High School. The research method uses qualitative with descriptive research type. The research was conducted at the Pekanbaru Telecommunications Junior High School with the research subjects being principals, teachers, students, and janitors. Data were collected through interview, observation and documentation techniques. The results showed that the Adiwiyata policy as the implementation of character education at the Telecommunications Junior High School in Pekanbaru was running well according to the goals set because it was carried out through the stages of character education development.